OPTIMIZATION OF CROPPING PATTERN IN IRRIGATED AREA GEMBLENG BANYUWANGI REGION USING DYNAMIC PROGRAM - Ahmad Rizza Lufafi; Wiwik Yunarni Widiarti; Entin Hidayah (Jurnal Rekayasa Sipil dan Lingkungan, 2020)
Gembleng Dam is located between Aliyan Village, Rogojampi District, and Parijatah Wetan Village, Srono District, Banyuwangi Regency. The dam was built to store water from the Bomo River. The Gembleng Dam is used for land irrigation with a service area of ±1735 Ha. During the dry season, The Gembleng irrigation often experiences drought and uneven water distribution. Therefore, optimization efforts using a dynamic program is used to optimize irrigation water so that it can increase yields. The results of this study are the water needed for irrigation every year is rice in rainy season 7,599 m3 / sec, rice in dry season I 7.93 m3 / sec, secondary corps in dry season II 5.35 m3 / sec for a possible year. The optimal cropping pattern is rice for rainy, rice and secondary corps for the first dry season, and secondary corps for the second dry season. The optimum land area that can be planted in a possible year is 849 ha of the dry season and 886 ha of secondary corps. For the normal year is 800 ha of rice and 935 ha of secondary corps. By using dynamic programming, the profit for enough years is Rp. 4,361,274,415.23 with an increase of 23.28%. Bendung Gembleng terletak di antara Desa Aliyan, Kecamatan Rogojampi dan Desa Parijatah Wetan, Kecamatan Srono, Kabupaten Banyuwangi, merupakan bendung yang dibangun untuk menampung air dari aliran sungai Bomo. Bendung Gembleng digunakan untuk memenuhi kebutuhan irigasi sawah dengan luasan baku sebesar ±1735 Ha. Ketika musim kemarau daerah irigasi Gembleng sering mengalami kekeringan dan pembagian air tidak merata. Oleh karena itu, upaya optimasi menggunakan program dinamik dilakukan untuk optimalisasi air irigasi sehingga dapat meningkatkan keuntungan hasil panen. Hasil dari penelitian ini berupa kebutuhan air untuk irigasi tiap tahun andalan yaitu, padi musim hujan 7,599 m3/dt, padi musim kering I 7,93 m3/dt, palawija musim kering II 5,35 m3/dt untuk tahun cukup. Pola tata tanam optimal yang diperoleh adalah padi, padi-palawija, dan palawija. Luas lahan optimum pada musim kering I yang dapat ditami pada tahun cukup untuk padi 849 ha dan palawija 886 ha. Keuntungan maksimal yang dapat diperoleh dari tiap tahun andalan yaitu sebesar Rp. 4.361.274.415,23 dengan peningkatan 23,28 % pada tahun cukup.